2018
DOI: 10.1016/j.jcrysgro.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

MOVPE growth of nitrogen- and aluminum-polar AlN on 4H-SiC

Abstract: We present a comprehensive study on metal-organic vapor phase epitaxy growth of N-polar and Alpolar AlN on 4H-SiC with 4 • miscut using constant growth parameters. At a high temperature of 1165 • C, N-polar AlN layers had high crystalline quality whereas the Al-polar AlN surfaces had a high density of etch pits. For N-polar AlN, the V/III ratio below 1000 forms hexagonal hillocks, while the V/III ratio over 1000 yields step bunching without the hillocks. 1-μm-thick m-thick N-polar AlN layer grown in optimal co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
(59 reference statements)
1
25
0
Order By: Relevance
“…The FWHMs increase with increasing the V/III ratio, suggesting degrading crystalline quality. Based on our previous study we believe this to be the optimum V/III ratio since hexagonal hillocks were formed when V/III ratio was decreased below 1000 [20]. We consider that the step flow growth mode contributes to high crystalline quality.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The FWHMs increase with increasing the V/III ratio, suggesting degrading crystalline quality. Based on our previous study we believe this to be the optimum V/III ratio since hexagonal hillocks were formed when V/III ratio was decreased below 1000 [20]. We consider that the step flow growth mode contributes to high crystalline quality.…”
Section: Resultsmentioning
confidence: 78%
“…In a previous study, we have shown that the formation of hexagonal hillocks can be suppressed in N-polar AlN growth by using a low growth rate of 0.1 µm/h together with an increased temperature of 1150 • C [20]. In this paper we study the effect of miscut angle of C-face 4H-SiC substrate on MOVPE growth of N-polar AlN under various growth conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Other studies have also confirmed that N-polar AlN usually coexists with Al-polar AlN IDs, meaning that AlN film grown on sapphire substrate generally exists in two forms: Al-polar AlN and mixed-polar AlN. To realize large-area pure N-polar AlN, C-face SiC substrate may be the better choice [24]. The mixed-polar AlN can be confirmed by the KOH solution etching because N-polar AlN has an obvious faster etching rate compared with Al-polar AlN.…”
Section: Polarity Control Of Aln/sapphire Templatementioning
confidence: 88%
“…AlN can be grown in two forms: film and bulk. AlN films have been fabricated by various methods, such as metal–organic vapour-phase epitaxy (MOVPE) 4 , 5 , hydride vapour phase epitaxy (HVPE) 6 , 7 , pulsed laser deposition (PLD) 8 , 9 , molecular beam epitaxy (MBE) 10 , 11 , or sputtering 12 , 13 , to improve its crystalline quality, surface area, growth rate, or lower its processing temperature. Annealing techniques have been demonstrated to improve the crystalline quality of AlN films 14 16 .…”
Section: Introductionmentioning
confidence: 99%